STRATEGI PENERAPAN TAX AMNESTY TERHADAP PENERIMAAN PAJAK (STUDI PADA KPP PRATAMA SIDOARJO UTARA) - RITMA LAILI, DEWI (Jurnal Akuntansi AKUNESA, 2017)
This study aims to explore the alternative strategies for KPP Pratama Sidoarjo Utara after the implementation of tax amnesty program, in order to support the success of the program. This study formulated the alternative strategy by using of Strength, Waekness, Opportunity and Threat (SWOT) Analysis and Internal External (IE) Matrix. This study finds that the position of KPP Pratama Sidoarjo Utara (KPP) is in growth and build (in the cell 2) of Internal External (IE) Matrix. Therefore, this study recommends that the KPP should use technology for tax dissemination to attracts taxpayers, encourage the maximization of technology utilize for taxpayers, evaluate the tax amnesty program comprehensively, encourage law enforcement after tax amnesty program intensively, expand tax base in range area of the KPP, arrange cooperation with foreign parties, government agencies and banks related to taxpayers data. The study implies that the KPP can increase tax revenue through intensive strategy by market penetration (tax intensification), market development (tax extensification) and product development (restructuring and tax reform). Keyword:, Strategy, Tax, Tax Amnesty, Tax Revenue